Meningkatkan Kesadaran Remaja Terhadap Stunting Melalui Psikoedukatif Di Lombok Timur - Husnawati, Husnawati; Azizah, Nurholik; Zulfiani, Hasaniah (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Stunting is a chronic nutritional problem that affects children's physical growth and cognitive development, and it remains a national priority issue in Indonesia. One of the key strategies for preventing stunting is to provide education to adolescent girls as future mothers, considering that their nutritional status greatly influences pregnancy outcomes and fetal growth. This community service activity aims to increase adolescent girls’ awareness of the importance of balanced nutrition and anemia prevention as a means of reducing stunting in future generations. The method used was socialization through interactive counseling sessions at several senior high schools in East Lombok Regency, targeting adolescents aged 14–18 years. The activities included material preparation, logistical arrangements, implementation of health education, and final reporting. The topics delivered covered balanced nutrition, anemia in adolescents, and the distribution of Iron-Folic Acid (IFA) tablets. The results showed that the counseling sessions effectively improved adolescents’ knowledge about stunting and the importance of adopting healthy lifestyle habits early on. Health education on stunting has proven to be a strategic approach to raising awareness and preparing adolescents for a healthy reproductive future. This activity is expected to serve as a model for involving adolescents in stunting prevention efforts, especially in East Lombok.